Case report of rare congenital cardiovascular anomalies associated with truncus arteriosus type 2. Issue 10 (October 2022) - Alizadeh, Leona S.; Koch, Vitali; Grünewald, Leon D.; Yel, Ibrahim; Mathies, Daniel; Rauschning, Dominic; Vogl, Thomas J.; Booz, Christian
Abstract: Truncus arteriosus (TA) is a very rare congenital anomaly with complex cardiovascular anatomy and high lethality also due to severe associated anatomical variants and pathologies. As TA has a massive impact on the survival of a newborn and usually has to be surgically treated. Thus, it is of high importance to understand this congenital cardiovascular disease and associated complications, to improve life expectancy and outcome of these patients. We recently came across a newborn female patient with a rare complex case of persistent TA type 2 associated with further complex cardiovascular anomalies, who received a contrast enhanced CT scan on the 3 rd day post-partum, showing complex cardiovascular abnormalities that were ultimately incompatible with life. Abstract : Truncus arteriosus; Fetal heart; Cardiovascular diseases; Heart defects, Congenital.